La edición del diálogo teatral (siglos XVI-XVII) - Pineda, Victoria; Giuliani, Luigi (Studi e saggi, 2021)
The contributions that compose this book were presented at the XIV Taller Internacional de Estudios Textuales (Perugia 2018), where different issues related to the transmission of Spanish Golden Age plays and its relevance for modern editing were discussed. The relationship between autograph manuscripts and prompt books, the usus scribendi of professional copyists, the textual variant readings in the transmission of printed texts, the importance of meter for establishing texts and proving authorships, the comparison of Spanish and Anglo-American editing practices, and the adaptation of plays for the modern stage, are all issues addressed by means of case studies that elucidate unexpected angles of textual criticism.